Soluciones extrañas en ecuaciones con radicales de índice 2 - Vaca Rosado, Ronald Edwin (2022)
Strange solutions appear by an incorrect procedure in the solution of equations involving even index radicals, due to the didactic transposition process. The traditional way of solving these equations was used, which is incorrect and leads to the appearance of strange solutions, it has many times to perform a check of the solutions in the original equation to see whether or not there is a strange solution; however, when using the respective theorems, do not appear evidences of strange solutions, therefore, there is no need to verify the solutions in the original equation.